Prevalence of Porcine Circoviruses in Slaughterhouses in Central Shanxi Province, China - Yue, Weidong; Li, Yilei; Zhang, Xinrong; He, Junping; Ma, Haili (Frontiers in Veterinary Science, 2022)
Background Porcine circovirus disease is currently the greatest threat to pig farming. Four main porcine circovirus genotypes are circulating worldwide. Objective The study aimed to assess the prevalence of porcine circovirus genotypes in the central part of Shanxi province. Methods We investigated the prevalence of porcine circovirus type 2 (PCV2), porcine circovirus type 3 (PCV3), and porcine circovirus type 4 (PCV4). Porcine circoviruses were analyzed by polymerase chain reaction (PCR) in the lung tissues of 180 pigs from 7 slaughterhouses in central Shanxi, China. Results The prevalence of PCV2, PCV3, and PCV4 were 56.8, 80, and 9.4%, respectively, and the negative rate was 10% for all three pathogens. The co-infection with PCV2 + PCV3, PCV2 + PCV4, PCV3 + PCV4, and PCV2 + PCV3 + PCV4 were 47.2, 7.4, 7.4, and 5.6%, respectively. Among PCV4-positive samples, the positive rate of PCV4 + PCV2 was 52.9% (9/17), whereas that of PCV4 + PCV3 was 100% (17/17). On the other hand, PCV2 and PCV3 were detected in 57.1% (93/163) and in 78.5% (128/163) of PCV4-negative samples, respectively. Phylogenetic analysis demonstrated that PCV2, PCV3, and PCV4 were not in the same clade and were distant from each other. Conclusion The high positive rates of PCV3, PCV2 + PCV3, and PCV3 + PCV4 suggest that PCV3 may play a decisive role in PCV2 and PCV4 infections. Therefore, further control of PCV3 is needed to reduce the spread of the virus.